2019
DOI: 10.3390/md17120710
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Secondary Metabolites from the Culture of the Mangrove-Derived Fungus Daldinia eschscholtzii HJ004

Abstract: Two new polyketides, 8-O-methylnodulisporin F (1) and nodulisporin H (2), two new naphthoquinones, 5-hydroxy-2-methoxy-6,7-dimethyl-1,4-naphthoquinone (3) and 5-hydroxy-2-methoxynaphtho[9–c]furan-1,4-dione (4), and a new naphthofuran 1,3,8-trimethoxynaphtho[9–c]furan (5), along with five known compounds 4-O-methyl eleutherol (6), 2-acetyl-7-methoxybenzofuran (7), (-)-orthosporin (8), diaporthin (9), and 6-hydroxymellein (10), were obtained from the EtOAc extract of the mangrove-derived fungus Daldinia eschscho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Wang et al [6] also found three new polyketides from mantis-associated fungus D.eschscholzii, named daldinone F (8), nodulisporin G (9), and dalmanol C (10). And then, Zhang et al [7] found a novel polyketide natural product named galewone (11)(12).…”
Section: Natural Products Of Various Species Of the Genus Daldiniamentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al [6] also found three new polyketides from mantis-associated fungus D.eschscholzii, named daldinone F (8), nodulisporin G (9), and dalmanol C (10). And then, Zhang et al [7] found a novel polyketide natural product named galewone (11)(12).…”
Section: Natural Products Of Various Species Of the Genus Daldiniamentioning
confidence: 99%
“…From the mangrove endophytic fungus D.eschscholtzii HJ001, Yang et al [10] obtained a new cytochalasin (15). And then, the group [11] isolated two new polyketides 8-O-methylnodulisporin F (16) and nodulisporin H (17), two new naphthoquinones, 5-hydroxy-2methoxy-6,7-dimethyl-1,4-naphthoquinone (18), and 5-hydroxy-2-methoxynaphtho [9-c] furan-1,4-dione (19), and a new naphthofuran 1,3,8-trimethoxynaphtho [9-c] furan (20). After that, this group [12] found five new tetralones, daldiniones…”
Section: Natural Products Of Various Species Of the Genus Daldiniamentioning
confidence: 99%
See 2 more Smart Citations
“…Fungi especially from unique ecological niches are capable of producing a variety of bioactive compounds [ 3 , 4 , 5 ]. Mangrove-derived endophytic fungi, as plant mutualists that occur in the tropical and subtropical intertidal estuarine zones, have attracted more attention of natural product chemists due to their production of structurally diverse and biologically active secondary metabolites [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Hypoxylon species are widespread in terrestrial and marine environments, and chemical investigations of some Hypoxylon spp.…”
Section: Introductionmentioning
confidence: 99%